A Unique 100 Meter Underwater Survey Method Documents Changes in Abundance, Richness, and Community Structure of Hawaiʹi Reef Fishes - Larson, Shawn; Christiansen, Jeff; Olsen, Amy Y.; Walsh, William J.; Teague, Christopher H.; Tissot, Brian; Randell, Zachary (Frontiers in Marine Science, 2022)
Hawai′i coral reefs are essential ecosystems providing resources in the form of food and recreation as well as stabilizing nearshore biodiversity. The Seattle Aquarium has exhibited Hawai′i reef fishes and corals since the mid-1980s to educate guests about these critical ecosystems. In 2009, and in collaboration with Hawai′i’s Division of Aquatic Resources (DAR) and Washington State University, the aquarium expanded its conservation work in Hawai′i through annual surveying of eight reefs along the west coast of Hawai′i via SCUBA-based diver operated video (DOV). Five of the sites are in areas partially closed to most fishing while three sites are in areas partially open to most fishing. 100-meter DOV surveys took place a meter above a horizontal or vertical reef, and survey locations were marked with GPS and fixed underwater markings to enable annual surveys to occur in the same locations. Counts of fish species were subsequently made from the archived video. Over the 11 year dataset we documented increased total abundance at all sites and periods of increasing and decreasing species richness. Multivariate analyses comparing fish community structure before (2009-2012) and after an anomalous warm-water event (2013-2019) documented a persistent shift in community structure. This coincides with a documented marine heat wave in Hawai′i and associated coral bleaching events between 2013-2016. These results suggest that our long-term monitoring program captured a phase shift in community structure associated with changing environmental conditions. These persistent shifts may thus indicate hysteresis at relatively short temporal scales, and ongoing monitoring is required to observe whether the systems shift back to the pre-2013 community structure. As coral reef ecosystems face a multitude of stressors from warming waters to marine pollution, long-term monitoring programs are essential to illuminate trends that may inform conservation and management strategies to preserve these imperiled ecosystems.